Saúde da mulher: Biomecânica Computacional para Enfrentar os Desafios Clínicos da Mama - Ana Margarida Correia da Rocha (2020)
The breast is an organ and exists in both sexes. It follows a similar course of development until puberty. After that, female breasts develops under the influence of pituitary hormones, ovaries, and others. Over the years, the breast structure changes, caused not only by its natural development (puberty, age, pregnancy, menopause), as well as due to the occurrence of pathologies [1]. Breast cancer is the higher incidence pathology in the USA and Western Europe, affecting mostly women [2]. To avoid the evolution of this disease, its early detection is crucial since it will allow an improved surgical process and treatment. With this, the study of diagnosis techniques is essential to improve its limitations and reduce possible false negatives that the techniques may provide. Elastography is one of the imaging techniques implemented in clinical practice. It Exists for more than 10 years, however, recently there has been a need to develop new studies based on it. Thus, it is intended that elastography can be considered as a standard technique for tumors diagnose. This technique can provide and evaluate the stiffness of tumors in the non-invasive way [3-5]. Together with computacional tools, it is intended to study the technique mentioned to acquire more sensitivity about it regarding the diagnosis of tumors. Through the Abaqus software using the Finite Element Method (FEM), a representative geometric model of breast was developed, which includes the skin, adipose tissue, fibroglandular tissue and muscle. With this model it is intended to study essentially the behavior of healthy tissues and benign and malign tumors of different dimensions in breasts with distinct densities, when subject to external forces,simulated the imaging technique strain elastography. Analyzing the values obtained, it is verified that when the dimension and stiffness of the tumor increases in the model implemented, the force along the compression exercised tends to increase. The same is verified when analyzed the Young modulus, that increase when the compression increases. It is concluded that for a maximum applied displacement of 11.4mm under the tissues, when nalyzed tumors of small dimension, the diagnosis can be a false negative. However, for the tumors with larger dimensions, the results suggest that the technique is able to have perception of the presence of possible tumors in the breast. [1] Gray, H. (2008)." The anatomical basis of clinical practice" 39th edition. Elsevier. [2] Torre LA, Siegel RL, Ward EM, Jemal A. Global cancer incidence and mortality rates and trends-an update. Cancer Epidemiol Biomark Prev.2016;25(1):16-27. [3] SAMSUNG Newsroom. "Exame de elastografia garante eficácia no diagnóstico de doenças de maneira rápida e indolor". (2017). Disponível em https://news.samsung.com/br/exame-de-elastografia-garante-eficacia-no-diagn[..]. Acesso em 10/janeiro/2020. [4] Sigrist, R. M. S., Liau, J., Kaffas, A. El, Chammas, M. C., & Willmann, J. K. (2017). T h e r a n o s t i c s Ultrasound Elastography : Review of Techniques and Clinical Applications, 7(5). https://doi.org/10.7150/thno.18650. [5] Barr, R. G. (2019). Future of breast elastography, 38(2), 93-105.